(untitled) - Fallon, Billy; Billy Fallon (Belmont, CA, 2007)
For the past two decades, Cecie Starr has been known as one of the best-selling biology textbook authors. Her texts, appreciated for their clarity in both the written word and the visual representation of biological concepts, include multiple editions of Biology: the Unity and Diversity of Life, Biology: Concepts and Applications, and Biology Today and Tomorrow. Her original dream was to become an architect. Instead of building houses, she now builds, with care and attention to detail, incredible texts based on this philosophy: "I invite students into a chapter through an intriguing story. Once inside, they get the great windows that biologists construct on the world of life. Biology is not just another house. It is a conceptual mansion. I hope to do it justice
Keywords: Human biology